2020
DOI: 10.1021/acs.jmedchem.0c00948
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Tyrosine Kinase 2 (TYK2) Inhibitor (PF-06826647) for the Treatment of Autoimmune Diseases

Abstract: Tyrosine kinase 2 (TYK2) is a member of the JAK kinase family that regulates signal transduction downstream of receptors for the IL-23/IL-12 pathways and type I interferon family, where it pairs with JAK2 or JAK1, respectively. On the basis of human genetic and emerging clinical data, a selective TYK2 inhibitor provides an opportunity to treat autoimmune diseases delivering a potentially differentiated clinical profile compared to currently approved JAK inhibitors. The discovery of an ATP-competitive pyrazolop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 44 publications
1
70
0
Order By: Relevance
“…Recently, a paper was published by Gerstenberger et al on the development of the selective TYK2 inhibitor PF-06826647 ( 34 ). In their paper, the authors describe having identified a determinant for the lower affinity of JAK inhibitors, such as tofacitinib, baricitinib and ruxolitinib, for TYK2 due to their pyrrolopyrimidine hinge-binding moiety.…”
Section: Klifs: Supporting Structure-based Kinase Researchmentioning
confidence: 99%
“…Recently, a paper was published by Gerstenberger et al on the development of the selective TYK2 inhibitor PF-06826647 ( 34 ). In their paper, the authors describe having identified a determinant for the lower affinity of JAK inhibitors, such as tofacitinib, baricitinib and ruxolitinib, for TYK2 due to their pyrrolopyrimidine hinge-binding moiety.…”
Section: Klifs: Supporting Structure-based Kinase Researchmentioning
confidence: 99%
“…The POI is selected based on prior knowledge of its biology, such as an implicated or established role in disease pathology. This allows for a rational approach, where compounds can be designed in silico, using molecular modeling, followed by synthesis and biochemical evaluation of compound-target binding [11]. Alternatively, in cases where it is hard to predict the compound binding site, a library of compounds or fragments (see Section 2.3) can be screened against the purified protein target [12,13].…”
Section: Target-based Approachesmentioning
confidence: 99%
“…In addition, preclinical studies demonstrated limited drug clearance via renal and biliary excretion in rats, and the major human clearance pathway for PF-06826647 was identified to be cytochrome P450 (CYP)-mediated (via CYP1A2, CYP2D6, and CYP3A) metabolism. 20 PF-06826647 has shown minimal inhibition of transporter proteins (i.e., MATE1, MRP1, MRP2, MRP3, sodium/Na+ taurocholate co-transporting polypeptide, OATP1B1, OATP1B3, and OCT2), with the exception of MATE2 inhibition. 20 In a phase I, first-in-human study (NCT03210961), we evaluated the safety, tolerability, and pharmacokinetics (PK) of PF-06826647 in healthy participants.…”
Section: Safety and Pk Of Oral Tyk2 Inhibitor Pf-06826647mentioning
confidence: 99%
“…20 PF-06826647 has shown minimal inhibition of transporter proteins (i.e., MATE1, MRP1, MRP2, MRP3, sodium/Na+ taurocholate co-transporting polypeptide, OATP1B1, OATP1B3, and OCT2), with the exception of MATE2 inhibition. 20 In a phase I, first-in-human study (NCT03210961), we evaluated the safety, tolerability, and pharmacokinetics (PK) of PF-06826647 in healthy participants. In this report, we present safety, tolerability, and PK data for escalating single and multiple doses of PF-06826647.…”
Section: Safety and Pk Of Oral Tyk2 Inhibitor Pf-06826647mentioning
confidence: 99%
See 1 more Smart Citation